Frontispiece: Diversifying Cross‐Coupling Strategies, Catalysts and Monomers for the Controlled Synthesis of Conjugated Polymers. Issue 50 (6th September 2018) - Baker, Matthew A.; Tsai, Chia‐Hua; Noonan, Kevin J. T.
Abstract : Catalyst‐transfer polycondensation has evolved rapidly in recent years to produce semiconducting materials in a precise manner. However, the number of monomers that can be polymerized using this method are still relatively limited. This Minireview highlights by K. J. T. Noonan et al. onpage 13078 ff. some of the developments in catalyst design for these polymerizations and offers considerations to polymerize more complex conjugated building blocks in the future.